2017
DOI: 10.1515/ppb-2017-0018
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and emotional predictors of episodic and dispositional forgiveness

Abstract: Abstract:The study examined the importance of cognitive (positive orientation, basic hope) (Thompson et al., 2005), TRIM (McCullough et al., 1998), P-Scale (Caprara et al., 2012), BHI-12 (Trzebiński & Zięba, 2003a), SUPIN (Polish version of PANAS;Watson, Clark, & Tellegen, 1988), CECS (Watson & Greer, 1983). Results showed that dispositional forgiveness (general and positive) was associated with cognitive and emotional predictors, whereas episodic forgiveness primarily with certain emotional variables. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…In line with our hypotheses, basic hope as well as aspects of forgivingness were inversely related with the level of depression. Our results are consistent with previous findings linking basic hope with depression [13], hope with dispositional forgiveness [31], and forgivingness with depression [51,52]. Moreover, we found evidence supporting the idea that dispositional forgiveness mediates the relationship between hope and depressive symptoms.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In line with our hypotheses, basic hope as well as aspects of forgivingness were inversely related with the level of depression. Our results are consistent with previous findings linking basic hope with depression [13], hope with dispositional forgiveness [31], and forgivingness with depression [51,52]. Moreover, we found evidence supporting the idea that dispositional forgiveness mediates the relationship between hope and depressive symptoms.…”
Section: Discussionsupporting
confidence: 93%
“…optimism about future in different areas, hope for achieving goals or as avoidance of hope threats, and none of them have examined basic hope. Nevertheless, Mróz and Kaleta [31] revealed a positive correlation between basic hope and dispositional forgiveness, while Trzebiński and Gruszecka [32] found that basic hope was negatively related to the tendency to seek vengeance and positively related to reconciliation with the wrongdoer.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the differences between these two types of forgiveness are highlighted by their relationships with different variables (e.g. Riek and Mania 2012;Mróz and Kaleta 2017).…”
Section: Discussionmentioning
confidence: 99%
“…So far only the adapted or translated versions of original English scales were used in the Polish research on forgiveness (e.g. Mróz and Kaleta 2017;Kossakowska and Kwiatek 2017;Charzyńska et al 2018;Kaleta and Mróz 2018). Meanwhile Polish culture is classified as a less individualistic than the culture of the United States and countries of Western Europe (Hofstede et al 2010), which may affect the understanding of forgiveness.…”
Section: Limitationsmentioning
confidence: 99%
“…Different studies show that basic hope correlates positively with optimism (Zięba, Czarnecka-van Luijken, & Wawrzyniak, 2010), the tendency to forgive (Mróz & Kaleta, 2017;Trzebiński & Gruszecka, 2012), and coping strategies, especially existential ones (Trzebiński & Zięba, 2003a). According to Ogińska-Bulik (2013), strong basic hope favors the ability to use life's opportunities.…”
mentioning
confidence: 99%